Bibliometric and visualized analysis of the applications of exosomes for bone regeneration - Ai, Shuai; Xie, Zhou; Li, Ningdao; Zhao, Runhan; Qu, Xiao; Zhou, Haining; Tang, Dagang; Zhang, Jun; Luo, Xiaoji (Frontiers in Cell and Developmental Biology, 2025)
BackgroundBone defect, a common orthopedic condition, is characterized by a lengthy and impactful treatment period, posing a considerable challenge in clinical settings. Medical technology has advanced notably, and has effectively treated an increasing number of patients with bone defects. Consequently, there has been an explosion of research articles on bone regeneration, including a substantial number on the application of exosomes. Exosomes, especially those derived from stem cells, have been confirmed to be effective in bone regeneration and have garnered widespread attention in the last decade. Therefore, this study conducted a bibliometric analysis on publications related to the application of exosomes for bone regeneration. The objectives are to explore the development history and research hotspots in this field over the past 10 years, predict future development trends, and provide guidance for subsequent research.MethodsThe Web of Science Core Collection (WoSCC) database was searched for articles related to exosomes and bone regeneration published from 1 January 2014, to 31 December 2023. The collected literature was analyzed using software such as Microsoft Excel, CiteSpace 6.3R1, VOSviewer 1.6.20, and the bibliometric online platform (https://bibliometric.com).ResultsA total of 3,004 articles published by 2,729 institutions from 68 countries were included in this study. The number of articles on the application of exosomes for bone regeneration has increased annually over the last decade. China was the most prolific country in this field, with a total of 1,468 papers; Shanghai Jiao Tong University (China) was the institution with the highest number of publications (117 publications). In terms of authors, Xin Wang, Yi Zhang, and Yang Wang were the three who published the highest number of papers, with 14 papers each. Co-citation analysis revealed that the article published by Valadi H in 2007 has the highest number of co-citations (270 times of quotation). Additionally, most research hotspots focused on the function of exosomes and the mechanism of action. Furthermore, the importance of osteoblast differentiation and angiogenesis in bone regeneration has also garnered significant attention from scholars in this field.ConclusionThis study reviewed the research achievements on the application of exosomes for bone regeneration over the past 10 years, utilizing bibliometric analysis tools. It visualized the countries, institutions, authors, and journals that have made significant contributions to this field, revealed current research hotspots, and finally explored future development trends.